PERAN PUBLIC SPEAKING PROFESIONAL DALAM MEMPROMOSIKAN ECO-BUSINESS INTELLIGENCE UNTUK PENINGKATAN RESILIENSI INDUSTRI KREATIF DI LAMONGAN - Nugroho, Dodit Cahyo; Manafe, Leonard Adrie; Zebua, Martin; Wibowo, Bambang Sri (LPPM ITB AAS Indonesia Surakarta, 2024)
The community service activity conducted at Moola Café, Lamongan, aimed to enhance the skills and knowledge of Micro, Small, and Medium Enterprises (MSMEs) in facing increasingly complex market challenges. Involving 10 MSME participants from various sectors, the seminar focused on improving communication skills, implementing eco-business intelligence, and developing sustainable business strategies. Through sessions on public speaking and effective communication, participants were encouraged to boost their confidence and ability to present their products. A questionnaire completed by participants identified the challenges faced, such as market access, funding, and knowledge of sustainability, as well as opportunities in creative product development and digital marketing. Collaborative discussions generated ideas for forming discussion groups, conducting joint training, and establishing marketing collaborations. The follow-up plan includes mentoring in the application of strategies based on the DEA+LCA FRAMEWORK, aimed at enhancing operational efficiency and reducing the environmental impact of their businesses. The results of this activity indicate an improvement in skills, a better understanding of sustainable practices, and strengthened networks among MSME participants. With continued support, it is hoped that MSMEs will become more adaptive and innovative, contributing to the sustainable growth of the creative industry in the Lamongan region. This activity successfully created an ecosystem that supports the development of MSMEs and enhances their competitiveness in a market increasingly demanding sustainability and innovation.